Cross-Hybridization of Closely Related Genes on High-Density Macroarrays - N.A. Miller; Q. Gong; R. Bryan; M. Ruvolo; L.A. Turner; S.T. LaBrie (BioTechniques)
DNA macroarrays are used in many areas of molecular biology research for applications ranging from gene discovery to gene expression profiling. As an increasing number of specialized macroarrays containing genes related by function or pathway are becoming available, a question that needs to be addressed is the level of hybridization signal specificity between highly similar genes that can be achieved. We have examined the ability of our LifeGrid™ macroarrays to distinguish hybridization signals between closely related genes. We determined the level of cross-hybridization among genes ranging from 52% to 94% sequence identity. Fragments of genes from five protein families were arrayed onto nylon filters. The filters were subsequently hybridized with a 33P-labeled probe prepared from a pool of synthetic mRNA transcripts containing a representative of each protein family. We found that fragments containing sequences with up to 94% sequence identity displayed relatively little cross-hybridization. We conclude that this macroarray system is very specific and that hybridization signals from closely related genes can be reliably measured.